Identification of novel biomarkers in chronic immune thrombocytopenia (ITP) by microarray‐based serum protein profiling. (2nd December 2015) - Bal, Gürkan; Futschik, Matthias E.; Hartl, Daniela; Ringel, Frauke; Kamhieh‐Milz, Julian; Sterzer, Viktor; Hoheisel, Jörg D.; Alhamdani, Mohamed S. S.; Salama, Abdulgabar
Summary: The pathological mechanisms underlying the development of immune thrombocytopenia (ITP) are unclear and its diagnosis remains a process of exclusion. Currently, there are no known specific biomarkers for ITP to support differential diagnosis and treatment decisions. Profiling of serum proteins may be valuable for identifying such biomarkers. Sera from 46 patients with primary chronic ITP and 34 healthy blood donors were analysed using a microarray of 755 antibodies. We identified 161 differentially expressed proteins. In addition to oncoproteins and tumour‐suppressor proteins, including apoptosis regulator BCL2, breast cancer type 1 susceptibility protein (BRCA1), Fanconi anaemia complementation group C (FANCC) and vascular endothelial growth factor A (VEGFA), we detected six anti‐nuclear autoantibodies in a subset of ITP patients: anti‐PCNA, anti‐SmD, anti‐Ro/SSA60, anti‐Ro/SSA52, anti‐La/SSB and anti‐RNPC antibodies. This finding may provide a rational explanation for the association of ITP with malignancies and other autoimmune diseases. While RUNX1 mRNA expression in the peripheral blood mononuclear cells (PBMC) of patients was significantly downregulated, an accumulation of RUNX1 protein was observed in the platelets of ITP patients. This may indicate dysregulation of RUNX1 expression in PBMC and megakaryocytes and may lead to an imbalanced immune response and impaired thrombopoiesis. In conclusion, we provide novel insights into the pathogenic mechanisms of ITP that warrant further exploration.